2023
DOI: 10.1001/jamaoncol.2022.7966
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Weekly Paclitaxel Plus Vistusertib vs Paclitaxel Alone in Patients With Platinum-Resistant Ovarian High-Grade Serous Carcinoma

Abstract: ImportancePatients with platinum-resistant or refractory ovarian high-grade serous carcinoma (PR-HGSC) have a poor prognosis and few therapeutic options. Preclinical studies support targeting PI3K/AKT/mTOR signaling in this setting, and a phase 1 study of the dual mTORC1/mTORC2 inhibitor vistusertib with weekly paclitaxel showed activity.ObjectiveTo evaluate whether the addition of vistusertib to weekly paclitaxel improves clinical outcomes in patients with PR-HGSC.Design, Setting, and ParticipantsThis phase 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 46 publications
(67 reference statements)
0
15
0
Order By: Relevance
“…The Original Investigation titled “Efficacy and Safety of Weekly Paclitaxel Plus Vistusertib vs Paclitaxel Alone in Patients With Platinum-Resistant Ovarian High-Grade Serous Carcinoma: The OCTOPUS Multicenter, Phase 2, Randomized Clinical Trial,” published online March 16, 2023, in the May 2023 print issue, has changed license status to open access (CC-BY-NC-ND license). This article has been updated online.…”
mentioning
confidence: 99%
“…The Original Investigation titled “Efficacy and Safety of Weekly Paclitaxel Plus Vistusertib vs Paclitaxel Alone in Patients With Platinum-Resistant Ovarian High-Grade Serous Carcinoma: The OCTOPUS Multicenter, Phase 2, Randomized Clinical Trial,” published online March 16, 2023, in the May 2023 print issue, has changed license status to open access (CC-BY-NC-ND license). This article has been updated online.…”
mentioning
confidence: 99%
“…Likewise, an adequate assessment of subpopulations according to specific characteristics—such as biomarkers—requires a minimum sample size of 50 patients per group . The OCTOPUS study would not meet this criterion. Thirteen patients expressed low PTEN, and 55 expressed high PTEN.…”
mentioning
confidence: 99%
“…To the Editor The OCTOPUS randomized clinical trial recently reported in JAMA Oncology by Banerjee et al compared the combination of weekly paclitaxel plus vistusertib (wP+V) vs paclitaxel monotherapy in patients with platinum-resistant ovarian high-grade serous carcinoma (PR-HGSC). A progression-free survival (PFS) improvement from wP+V was predicted for patients with low tumor cell phosphatase and tensin homolog (PTEN) expression.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in our study, 70 women per group were recruited, which would meet the minimum sample size mentioned by Gil-Sierra and colleagues. However, as with all translational analyses, some samples failed the quality checks and were unusable for further analyses.…”
mentioning
confidence: 99%